MUTU LAYANAN MENURUT PELANGGAN LABORATORIUM KLINIK (Service Quality Regarding to The Clinical Laboratory Customer) - Mohammad Rizki; Osman Sianipar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Customer satisfaction survey for outpatient laboratory customer is routinely carried out in Clinical Laboratory InstallationRSUP Dr. Sardjito using modified SERVQUAL questionnaire. One advantage of using SERVQUAL is service provider will be able to monitorits service quality dynamics using standardized tool. Changes in one’s service quality can be measured using perceived quality changesbased on gap scorebetween different periods. All these years, RSUP Dr. Sardjito has not evaluated gap score changes in all survey period.This study aims to know service quality measured by perceived service quality on Customer Satisfaction Survey Period of Semester II2013 and Semester I 2014 by comparison. This is an observational non-experimental study using data from Customer SatisfactionSurvey in Clinical Laboratory Installation RSUP Dr. Sardjito Semester II 2013 and Semester I 2014. Data was analysed using SERVQUALmethod and presented descriptively as text and table. There were 231 and 229 responders respectively in Customer Satisfaction SurveySemester II 2013 and Semester I 2014. There were decreases in all but empathy service dimension. Decrease of expectation was foundin all SERVQUAL dimensions. The decrease of expectation exceeded perception decrease resulting in a rise of gap score from Semester II2013 to Semester I 2014 hence indicating an improvement of perceived service quality. There was an improvement of perceived servicequality according to external customer of Clinical Laboratory Installation RSUP Dr. Sardjito in Semester I 2014 compared to SemesterII 2013.